Polemik Dana Aspirasi Dalam Perspektif Politik Hukum Penganggaran Indonesia - Erawati Erawati (Simbur Cahaya, 2020)
In addition to being considered prone to corrupt practices, the existence of aspirational funds is deemed to have deviated from the existing legal corridors of state administration and legislation, bearing in mind that the authority of the DPR which was "able" to submit budget proposals in Article 15 of Act 17 of 2003 concerning State Finance, became " entitled to "propose and fight for the development of electoral districts in Law 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council or better known as the MD3 Law. This implies an expansion of the DPR Budget right from what was originally limited to "accepting and rejecting" to also include the realm of "proposing", as well as reinforcing the tendency of the legislative heavy in the Indonesian budgeting system. This article aims to determine the existence of aspiration funds in the political perspective of Indonesian budgeting law. This study uses normative research methods by obtaining information from various sources of legal rule literacy, legal principles, and legal doctrines, to produce new arguments, theories, or concepts as a description in analyzing how the existence of aspirational funds when viewed from a political perspective Indonesian budgeting law. The results showed, the existence of aspiration funds made the checks and balances mechanism ambiguous, created inequalities in development and new injustices, and in addressing the issue of aspiration funds, solidity and firm attitudes of the government were needed while still referring to existing development plans.